2007
DOI: 10.1068/a38283
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Homicide in São Paulo, Brazil

Abstract: The authors investigate geographical patterns of homicide in São Paulo, Brazil. The geography of crime in developing world cities has been an underresearched area in part because of the lack of good-quality, geocoded offence data. In the case of São Paulo the availability of a new digital police dataset has provided the opportunity to improve our understanding of its crime patterns. The authors report the testing of hypotheses about the spatial variation in homicide rates. This variation is explained by povert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 44 publications
3
52
0
6
Order By: Relevance
“…To analyze the influence of alcohol outlets on violent crime in nearby small-areas, we constructed spatially lagged variables for on-and off-premise outlets. Spatial lag refers to the average of alcohol outlet measurements in adjacent DAs and for on-premise outlets was measured through outlet density and for off-premise outlet was measured through the average of absence/ presence (Zhu et al 2004;Gorman et al 2001;Livingston 2008;Ceccato et al 2007).…”
Section: Study Region and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the influence of alcohol outlets on violent crime in nearby small-areas, we constructed spatially lagged variables for on-and off-premise outlets. Spatial lag refers to the average of alcohol outlet measurements in adjacent DAs and for on-premise outlets was measured through outlet density and for off-premise outlet was measured through the average of absence/ presence (Zhu et al 2004;Gorman et al 2001;Livingston 2008;Ceccato et al 2007).…”
Section: Study Region and Datamentioning
confidence: 99%
“…Alcohol outlets are one land use type that has often been found to be associated with violent crime (Livingston et al 2007), as they are hypothesized to be locations where large numbers of potential offenders and targets converge under the influence of alcohol (Kinney et al 2008;Kurtz et al 1998;Cohen et al 2008;Ceccato et al 2007), and because they are often located in areas where local social control is not capable of regulating criminal behaviour (Britt et al 2005;Conley et al 2014;Lipton and Gruenewald 2002). Using a Bayesian spatial regression modeling approach, this research analyzes the association between reported violent crime and on-premise and off-premise alcohol outlets at the small-area scale in the Region of Waterloo, Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme estudo recente 35 , boa parte dessa região é caracterizada por prédios comerciais, hotéis, restaurantes, cinemas e hospitais, são lugares que concentram muitas pessoas durante o dia. Essas áreas possuem ou estão localizadas próximas a terminais de transportes (metrôs e ônibus) e têm uma atividade noturna intensa em bares, casas de bingos, casas de prostituição (saunas); além disto, está rodeada de cortiços e concentram um grande mercado de drogas.…”
Section: Estimação Da Superfície Do Risco De Homicídiounclassified
“…Os resultados apresentados são condizentes com estudos recentes 7,35 e a estrutura urbana da cidade, não à guisa de conclusão, mas como uma forma alternativa de auxiliar na compreensão da distribuição espacial do risco de homicídio e poder contribuir para os meios de vigilância e prevenção. Embora a explicação da distribuição do fenômeno investigado seja complexa, existem diversos fatores que podem contribuir para explicar esta distribuição, tais como: índice de concentração de renda; taxa de evasão escolar; diferenças nas taxas de desemprego entre os jovens; distribuição de equipamentos públicos como escolas, parques, hospitais e outros.…”
Section: Comentários Finaisunclassified
“…Así, se han registrado mayores tasas de criminalidad en zonas donde se llevan a efecto altos volúmenes de transacciones comerciales, lo cual probablemente atraiga a los criminales por la mayor presencia de una oportunidad para delinquir (vilalta, 2009a;Ceccato et al, 2007). Entre los problemas económicos locales, a la criminalidad se le ha relacionado con los descensos en los niveles de empleo, variables por zonas de la ciudad (Morenoff y Sampson, 2007;Ackerman, 1998;Sampson y Wilson, 1995).…”
unclassified